Implementasi deep learning pada mata pelajaran PKn untuk menumbuhkan nilai karakter di sekolah dasar - Mutiara Dana Elita; Nurratri Kurnia Sari; Ersandya Vinne; Eka Putri Angraeni (Universitas PGRI Madiun, 2026)
Character education has become an urgent need in elementary schools amid declining moral values among some students, while Civic Education (PKn) plays a strategic role in instilling such values. The Ministry of Primary and Secondary Education's Regulation No. 13 of 2025 integrates a deep learning approach into the curriculum, yet studies specifically linking its implementation to PKn in elementary schools for character development remain limited. This study aims to describe the implementation of the deep learning approach in PKn learning at the elementary level and analyze its contribution to fostering students' character values. This study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines, searching articles published in 2021–2026 indexed in SINTA 1–3 and Scopus via Google Scholar. The synthesis results show that deep learning implementation in PKn is generally student-centered, employing group discussions, problem solving, project-based learning, contextual learning, and reflection, with teachers acting as facilitators. This approach positively contributes to strengthening discipline, responsibility, cooperation, honesty, tolerance, mutual cooperation, nationalism, and democratic attitudes, while also improving conceptual understanding and active student engagement. This study recommends more diverse research designs and broader regional coverage for future studies.